Summary report on the evaluation of short-term tests for carcinogens: collaborative study on in vivo testsCarcinogens, summary report on the evaluation of short-term in vivo tests (Environmental health criteria)
El texto completo se encuentra disponible en la página: http://www.inchem.org/pages/ehc.html